The effect of political instability and institutional weakness on administrative corruption - Salem A. Al-Jundi; Ahmed Shuhaiber; Shaban S. Al-Emara (Contemporary Economics, 2022)
Although there is valuable literature on areas of corruption, such as political and corporate corruption, a limited number of papers have examined the determinants of administrative corruption. To the best of our knowledge, the multivariate impacts of political instability and institutional weakness on administrative corruption, and the interplay between these constructs, have not been examined using the partial least squares structural equation modeling method. The current study attempts to fill this gap by proposing and testing a model. We test a sample of 677 responses that reflect the perspective of the general public in Basra, Iraq. Findings reveal that the political instability and institutional weakness of public organizations positively impact administrative corruption, while political instability leads to institutional weakness. Institutional weakness mediates the effect of political instability on administrative corruption. Therefore, political instability is a crucial factor causing corruption since it has both direct and indirect effects on administrative corruption. The theoretical contributions, managerial implications, limitations, and recommendations for further research are provided.
Keywords: C30; H11; O17; 330; Administrative corruption; political instability; institutional weakness; structural equation modeling; partial least squares